The Protein 4.1, Ezrin, Radixin, Moesin (FERM) Domain of Drosophila Coracle, a Cytoplasmic Component of the Septate Junction, Provides Functions Essential for Embryonic Development and Imaginal Cell Proliferation. - Ward, R.E.; Schweizer, L.; Lamb, R.S.; Fehon, R.G. (Genetics, 2001)
Coracle is a member of the Protein 4.1 superfamily of proteins, whose members include Protein 4.1, the Neurofibromatosis 2 tumor suppressor Merlin, Expanded, the ERM proteins, protein tyrosine phosphatases, and unconventional myosins. Recent evidence suggests that members of this family participate in cell signaling events, including those that regulate cell proliferation and the cytoskeleton. Previously, we demonstrated that Coracle protein is localized to the septate junction in epithelial cells and is required for septate junction integrity. Loss of coracle function leads to defects in embryonic development, including failure in dorsal closure, and to proliferation defects. In addition, we determined that the N-terminal 383 amino acids define an essential functional domain possessing membrane-organizing properties. Here we investigate the full range of functions provided by this highly conserved domain and find that it is sufficient to rescue all embryonic defects associated with loss of coracle function. In addition, this domain is sufficient to rescue the reduced cell proliferation defect in imaginal discs, although it is incapable of rescuing null mutants to the adult stage. This result suggests the presence of a second functional domain within Coracle, a notion supported by molecular characterization of a series of coracle alleles.